Estimasi Dampak Konsumsi Bahan Bakar Kendaraan pada Perlintasan Sebidang Kereta Api Kota Bandar Lampung - Indrawati, Titi; Usman, Kristianto; Sulistyorini, Rahayu (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Delays and vehicle queues are often observed during the closure of railway crossing gates, causing an increase in the time required to pass through a road section. Delays at level crossings lead to traffic congestion and fuel wastage for vehicles. Therefore, a case study on traffic volume is necessary to understand traffic conditions and analyze fuel consumption at railway level crossings. This research was carried out at level crossings on Urip Sumoharjo and Kamboja roads. The survey was carried out over three days on Tuesday and Thursday to represent weekdays, Sunday to represent weekends. Vehicle fuel consumption analysis used the ATIS India and IJIRT methods. The analysis results showed that fuel consumption using the ATIS India and IJIRT methods indicated that the level crossing on Urip Sumoharjo Street had the highest loss value, with an average fuel consumption during the study of 101,08 liters/hour for the ATIS India method and 108,91 liters/hour for the IJIRT method.